Do shocks affect men's and women's assets differently? Evidence from Bangladesh and Uganda - Quisumbing, Agnes R.; Kumar, Neha; Behrman, Julia A. (Wiley, 2018)
Using panel data, this article tests whether shocks affect men's and women's assets differently in Bangladesh and Uganda. Across countries, covariate and idiosyncratic shocks have different effects on men's, women's and jointly owned assets. Jointly held land and assets were better insured against food price increases in Bangladesh, unlike jointly held assets and wives’ assets in Uganda. Weather shocks affect husbands’ and wives’ assets differently in both countries. Reflecting contextual differences, illness shocks negatively affected wives’ land in Bangladesh, while death reduced husbands’ non‐land assets. In Uganda, fuel price increases eroded husbands’ landholdings, while drought shocks reduced wives’ assets. Ugandan husbands’ assets were better protected against covariate shocks than wives’ assets.